KEMAMPUAN KONEKSI MATEMATIS SISWA DITINJAU DARI GAYA KOGNITIF PADA MATERI PERSEGI PANJANG DI SMP - Sari, Octaviani Mustika; Yusmin, Edy; Nursangaji, Asep (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is aimed to describe students? mathematical connections ability viewed from cognitive style on rectangular material in Junior High School 23 Pontianak. The research method is descriptive with case study. The subject of this research are four students grade VIII E consist of two field dependent cognitive style students and two field independent cognitive style students. The results of this research are the field independent cognitive style students has a better mathematical connections ability than the field dependent cognitive style students. One of the field dependent cognitive style students able to fulfilled three indicators of mathematical connections and one of other the field dependent cognitive style students not able to fulfilled the indicators of mathematical connections. Meanwhile one of the field independent cognitive style students able to fulfilled three indicators of mathematical connections and one of other the field independent cognitive style students able to fulfilled two indicators of mathematical connections.Keywords: Mathematical Connections Ability, Cognitive Style, Rectangular